Use of adaptive servo ventilation therapy as treatment of sleep-disordered breathing and heart failure: a systematic review and meta-analysis - Hernandez, Adrian V. (2020)
Purpose: Adaptive servoventilation (ASV) has been reported to show improvement in patients with sleep-disordered breathing (SDB) and heart failure (HF); however, its role as a second-line or adjunctive treatment is not clear. We conducted a systematic review and meta-analysis of new existing data including cardiac mechanistic factor, geometry, and cardiac biomarkers. Methods: We systematically searched for randomized controlled trials (RCTs) and cohort studies that assessed the efficacy or effectiveness of ASV compared to conventional treatments for SDB and HF in five research databases from their inception to November 2018. Random-effects meta-analyses using the inverse variance method and stratified by study design were performed. Results: We included 15 RCTs (n = 859) and 5 cohorts (n = 162) that met our inclusion criteria. ASV significantly improved left ventricular ejection fraction (LVEF) in cohorts (MD 6.96%, 95% CI 2.58, 11.34, p = 0.002), but not in RCTs. Also, the ASV group had significantly lower apnea-hypopnea index (AHI) in both cohorts (MD − 26.02, 95% CI − 36.94, − 15.10, p < 0.00001) and RCTs (MD − 21.83, 95% CI − 28.17, − 15.49, p < 0.00001). ASV did not significantly decrease the E/e′ ratio in RCTs or in cohorts. Finally, ASV significantly decreased brain natriuretic peptide (BNP) in the cohorts (SMD − 121.99, CI 95% − 186.47, − 57.51, p = 0.0002) but not in RCTs. ASV did not have a significant effect on systolic blood pressure, diastolic blood pressure, and cardiac diameters. Conclusions: ASV therapy is associated with improvements of AHI in comparison to alternative treatments in patients with SDB and HF. ASV did not improve LVEF or E/e′ ratios in randomized trials; other intermediate outcomes did not improve significantly.